Social Network Effects and Green Consumerism - Dominic Hauck; Erik Ansink; Jetske Bouma; Daan van Soest (Tinbergen Institute, 2014)
One of the drivers of green consumerism are social network externalities that are associated with buying 'green' because green consumerism is fashionable, or because of reputation effects. We analyze how the strength of this social network effect impacts green consumerism, environmental externalities and total welfare. We discuss a model where products are differentiated according to their environmental quality, where the production of green products generates positive externalities to all, and where those consumers purchasing a green product variety receive the additional benefits of being a member of the network of green consumers. Depending on the strength of the social network effect, we show that (a) firms may produce lower quality, (b) the market may generate fewer positive environmental externalities, and (c) total welfare may deteriorate. The main policy implication is that if there is a network effect, regulators should choose a stricter minimum environmental quality standard.
Keywords: D11; L15; Q31; 330; Quality Differentiation; Social Network Effect; Minimum Environmental Quality Standard